Role of Physical and Cognitive Factors in Passing Abilities of Futsal Athletes in Universitas Padjadjaran (Majalah Kedokteran Bandung, 2019)
Futsal is a variation of soccer, to be played on a smaller field, with the fastest development among other indoor sports. Futsal players need to master several basic playing techniques to be able to play good futsal, one of them is passing. There are 2 factors that affect futsal athlete skills; physical and mental factors, including cognitive factors. This study aimed to determine the contribution of physical and cognitive factors on the ability to execute passing techniques. A cross-sectional analytic study was conducted in October 2018 on 33 participants who were listed as futsal players in the Faculty of Medicine Futsal Unit, Universitas Padjadjaran, and in the amateur futsal club, La Coruna FC. Physical factor data consisting of body muscle mass percentage, leg muscle percentage, total body fat percentage, and legs subcutaneous fat percentage were measured using Body Impedance Analysis tool while the cognitive factors consisting of; attention, short term memory, and spatial ability, were measured using grid concentration test, digit span test, and spatial ability test, respectively. Athlete’s passing ability was measured using 30 second pass and stop test. Data were then analyzed using regression analysis. The results showed that the percentage of leg muscles has the highest significance value for the athlete’s passing ability. (Î²=0.6, p
Keywords: Cognitive factor; futsal; passing ability; physical factor